External treatment of Traditional Chinese Medicine in the treatment of chalazion in a child and related nursing measures (中医外治治疗儿童霰粒肿1例的护理体会) - FENG Xiaohui (冯小慧); YIN Kexin (尹可欣); YANG Tingting (杨婷婷); TANG Ling (唐玲); LI Ye (李野); DUAN Yixuan (段怡璇) (中西医结合护理)
This paper summarized the nursing experience of external treatment of Traditional Chinese Medicine (TCM) in treating chalazion in children, including routine care, ear-tip bloodletting, Chinese herbal medicine hot compress, etc. The TCM external treatment, characterized by easy–to-use, obvious efficacy and high patient acceptance, is effect to relieve the inflammatory response caused by chalazion. (本文总结耳尖放血联合中药热敷治疗小儿霰粒肿的相关经验, 包括常规护理、耳尖放血操作方法、中药组方以及热敷方法等。中医外治法操作简单、疗效明显, 且具有较好的依从性, 能够有效缓解霰粒肿炎症反应, 减轻患儿痛苦。)